King in limbo. 1 - Tanaka, Ai (Kodansha USA, 2024)
"Eight years have passed since the sickness known as 'the Sleep' ended millions of lives. Now, after a dangerous procedure that involves diving into patients' memories has ended the pandemic, Petty Officer Adam Garfield wakes up in a hospital to find a bomb has taken one of his legs. But Adam's plan to retire from U.S. Navy service and cash in his pension to goof around with his younger siblings is shattered when he receives secret word that the sleeping sickness has returned, and it's his job to coax back the mysterious man who helped cure it the first time: a man known by the codename 'King'"--Cover.